Multifunctional polyethylene (PE)/polypropylene (PP) bicomponent fiber filter with anchored nanocrystalline MnO2 for effective air purification. Issue 30 (18th July 2018) - Dai, Zijian; Su, Jiafei; Zhu, Xiaoming; Xu, Kangli; Zhu, Jie; Huang, Chen; Ke, Qinfei
Abstract : A multifunctional composite filter combined with nanocrystalline MnO2 and a PE/PP bicomponent fiber by introducing corona charge technology has been fabricated and exhibited excellent filtration, adsorption and catalytic abilities in air pollutant abatement. Abstract : The fabrication of multifunctional fiber filters for passive room air purification via filtration, adsorption and catalytic mechanisms is critical to cater to urgent needs in the current air filter industry. However, few studies have concentrated on the construction of primary filters or medium-efficiency filters with versatile performance. Here, we constructed a multifunctional composite filter combined with nanocrystalline MnO2 and PE/PP bicomponent fibers by introducing corona charging technology. We utilized a novel redox process to synthesize α-MnO2 and δ-MnO2 with outstanding catalytic capacity for HCHO. The δ-MnO2 synthesized via the redox method was proved to possess the highest content of manganese vacancies, species and mobility of adsorbed oxygen. Thereby, the δ-MnO2 exhibited the best HCHO oxidation performance at low temperatures and was further chosen to fabricate an MnO2 /PE/PP carded filter with filtration, adsorption and catalytic abilities. Benefiting from a through-air bonding procedure, a fluffy PE/PP nonwoven mat with uniform dispersion and anchoring of MnO2 was constructed. An as-prepared MnO2 /PE/PP swatch exhibited excellent catalytic activity for HCHO, including complete oxidation within 60 min and acceptable reversibility over 5 cycles. Moreover, after corona charging an MnO2 /PE/PP sample exhibited a relatively high filtration efficiency of 71.73%, a low pressure drop of 6.02 Pa and an improved quality factor of 0.2219 Pa −1 . Because the manufacture of this MnO2 /PE/PP filter does not involve tedious procedures and would easily enable mass production, we expect that the methodology for fabricating the MnO2 /PE/PP filter with more functionalities and a higher charge retention capacity might facilitate the creation of advanced fiber filters.